PENSION REFORM ACTS AND PERFORMANCE OF INSURANCE INDUSTRY IN NIGERIA, 2004-2020 - Opara, Godstime Ikechukwu; Dim, Henry Chinedu (African Journal of Social and Behavioural Sciences, 2022)
This research work investigated the effect of pension reform acts on the performance of the insurance industry in Nigeria from 2004-2020. The study had four specific objectives: to analyze the effect of pension fund contributions from the public sector, pensions fund from the private sector, economic growth, inflation rate on insurance industry‟s gross premium income which was used as a measure of performance of the insurance industry. The sample size comprised all the 47 insurance companies registered with the National Insurance Commission (NAICOM). The data were analyzed using the Autoregressive Distributed Lag (ARDL) model and the findings revealed that public sector pension contribution under the pension reform act decreased gross premium income of the insurance industry both in the short and long run. Private sector pension contribution had positive effect on gross premium income of the insurance industry but was only significant in the long run. While the prevailing economic condition (real GDP) increased insurance gross premium, inflation rate exerted negative effect. The study concluded that the private sector pension contributions increased insurance premium income more than the public sector and that pension‟s portfolio was being affected by inflation rate. It was recommended that more insurance companies be encouraged to participate in pension matters as PFAs, public sector pension‟s contribution should be promptly remitted and that pension funds should be securitized on long term non-volatile securities.